(untitled) (Jurnal Geomine, 2016)
This research emphasis on geometry of the streets in the width of the road and grade roads. The purpose of this research was to obtain the geometry of the streets are made in accordance with the standards, to get the tilt lengthwise (grade). The method of research done in the field, namely by measuring the road hauling until towards the mining front taking into account distance, width, and slope by adjusting the technical calculation, then standardization of such data processed using autocad 2007 so as to facilitate the process of analysis. The process of data capture in the field by doing observation directly regarding a case study like doing the measurement distance, width, and the slope of the ramp and the supporting activities such as transportation aspects see Transport tool used in the field. Results of the study suggested that the width of the road transport to the State of straight i.e. 5 m and 9 m while in a State of bend i.e 8.11 m and 14.25 m. the conclusion that the State obtains the width of the road at STA 57 – 58 still experience a shortage of 4 m, and should be done in addition, namely by 1 m and slope extends on STA 9 – 10 i.e. reaching 30.48% and cutting must be carried out by 25%.